PARTISIPASI MASYARAKAT DALAM PENANGGULANGAN BANJIR DI KOTA PEKANBARU - Wahyu Rio Santoso; Sujianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Wahyu Rio Santoso, 1001135934 public participation in flood prevention in the city ofPekanbaru. Supervisor Prof. Dr. H. Sujianto. M. Si the Flooding problems in the city ofPekanbaru has become a serious concern for officials and experts spatial City lately.Therefore, almost every certain months of the regular flooding greets residents of Pekanbaru.Mainly when rainfall exceeds the capacity of the ground already covered most cities andpavin cement block. Even so, in fact unreasonable Pekanbaru city could be flooded. Becausethe position is located far above the surface of the Siak river is about 4 or 5 feet above thesurface of the Siak river, except in the northern area of town around the coastal fringe urbandistricts meranti pandak. Factor cause flooding can be caused naturally and also due to thechange. In urban areas the dominant cause of the flooding is a result of human activities thatcause spatial changes and impact on natural changes. Environmental degradation such asloss of vegetation cover in the catchment area of soil, siltation of rivers due to sedimentation,the narrowing of the river channel and so on can also be caused due to human action. Theconcept of the theory is that researchers use community participation, Angell theory in Rossand Holil are the factors that influence the community participation. while the researchmethodology is divided into: the study site is in a handsome village kecematan luck works,the type of research that is taking a qualitative approach with descriptive methods,informants, types and sources of data put on primary data and secondary data, and datacollection techniques. From the above research results will be obtained as follows: publicparticipation is a form of energy, a thought, and possessions. While external factors arecommunication, social climate, economic, political and cultural as well as the opportunity toparticipate and creative freedom, while internal factors are age, gender, education,employment, and income as well as the duration of its implementation in tackling floodtinggal. is planning, determination plan, control and evaluation of the implementation of theplan implementation plans.Keywords: Participation, Flood. Society